Pegaruh Lingkungan Kerja dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Pada JNE Sub Agen Klaten - Prema Vidya Santi; Bangun Putra Prasetya (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This research aims to determine the influence of the work environment and work discipline on employee productivity at JNE Klaten Sub Agent located in Klaten. The sample used as respondents was the entire population of employees at JNE Klaten Sub Agent. The data collection technique in this research was by distributing questionnaires to respondents. The statistical analysis method used in the research is instrument testing, classical assumptions followed by regression testing, hypothesis testing. The results of the hypothesis test of the work environment do not have a significant effect on work productivity, the t count value is 0.795 < t table 2.040. The results of the hypothesis test that work discipline has a significant effect on work productivity, the t count value is 4.258 > t table 2.040. The work environment and work discipline together have a significant effect on work productivity, the results of the multiple linear regression equation are Y= 0.717 + 0.112X1 + 0.641X2 + ē, with a calculated f value of 4.191 > 2.911 f table.